Extraction,purification and characterization of amylase,protease,lipase of halophilic bacterial isolates from Bordi, India - VIKAS JOSHI; anupama pathak; Supriya murkute; Bhoomi Das; zeenat khan (International Journal of Applied Biology, 2022)
Extremely halophilic isolates were obtained from mangrove vegetation of west coast Bordi region, Maharashtra India. All six isolates were selected for further investigation on the basis of their potential of producing enzymes amylase, protease and lipases respectively. Production of enzyme from isolates was performed using basal medium with starch, skimmed milk and tributyrin. Ammonium sulphate salt precipitation and dialysis was performed to obtain partially purified crude samples of enzymes. Activity of crude enzymes was determined in unit/ml by using standard methods. Also the effect of pH and temperature on enzyme activity was also determined.